2019
DOI: 10.1016/j.jaci.2018.08.052
|View full text |Cite
|
Sign up to set email alerts
|

Engulfment of mast cell secretory granules on skin inflammation boosts dendritic cell migration and priming efficiency

Abstract: Background: Mast cells (MCs) are best known as key effector cells of allergic reactions, but they also play an important role in host defense against pathogens. Despite increasing evidence for a critical effect of MCs on adaptive immunity, the underlying mechanisms are poorly understood. Objective: Here we monitored MC intercellular communication with dendritic cells (DCs), MC activation, and degranulation and tracked the fate of exocytosed mast cell granules (MCGs) during skin inflammation. Methods: Using a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 51 publications
2
34
0
Order By: Relevance
“…d.) injection of MC granules into MC-deficient mice was sufficient to induce a profound expansion of T cells indicating their adjuvant effect.Extending the finding of Kunder et al[65], we provided evidence that MC degranulation in the periphery may exert long-distance effects on LN-borne adaptive T cell responses in two ways:(a) trafficking of MC granules via lymphatic vessels towards the DLNs, and (b) active shuttling of MC granules by DCs along with DC modulating effects[64].Beside MC granules, MC-derived exosomes offer an additional mechanism for intercellular communication, by having greater stability in the interstitial space compared to soluble mediators[69,84] and being able to promote DC maturation and antigen-presenting capacity[85,86].Confirming our findings in CHS, Otsuka et al showed impaired skin DC maturation and migration in the absence of MCs and the relevance of a direct interaction between DCs and MCs, leading to an upregulation of membrane-bound TNF by MCs [87]. Given the close proximity of MCs and DCs in peripheral tissues, especially in the skin, a physical cell-to-cellinteraction was considered likely and studied in several in vitro studies.…”
supporting
confidence: 72%
See 1 more Smart Citation
“…d.) injection of MC granules into MC-deficient mice was sufficient to induce a profound expansion of T cells indicating their adjuvant effect.Extending the finding of Kunder et al[65], we provided evidence that MC degranulation in the periphery may exert long-distance effects on LN-borne adaptive T cell responses in two ways:(a) trafficking of MC granules via lymphatic vessels towards the DLNs, and (b) active shuttling of MC granules by DCs along with DC modulating effects[64].Beside MC granules, MC-derived exosomes offer an additional mechanism for intercellular communication, by having greater stability in the interstitial space compared to soluble mediators[69,84] and being able to promote DC maturation and antigen-presenting capacity[85,86].Confirming our findings in CHS, Otsuka et al showed impaired skin DC maturation and migration in the absence of MCs and the relevance of a direct interaction between DCs and MCs, leading to an upregulation of membrane-bound TNF by MCs [87]. Given the close proximity of MCs and DCs in peripheral tissues, especially in the skin, a physical cell-to-cellinteraction was considered likely and studied in several in vitro studies.…”
supporting
confidence: 72%
“…By means of MC granule staining in vivo, directly inside the MCs, and intravital 2-photon-microscopy, we could monitor MC degranulation and track the fate of MC granules after their exocytosis. We found that upon skin inflammation, dermal DCs accumulate at the site of MC degranulation, engulf the intact MC granules and shuttle them actively to skin-DLNs [64]. The MC granule uptake facilitates DC migration and maturation, and boosts the T cell priming capacity.…”
Section: Mcs Affect Adaptive Immunity Via the Modulation Of Dendriticmentioning
confidence: 92%
“…Secretion of granules containing inflammatory molecules is known to be one of the primary mechanisms employed by MCs. Degranulation elicits inflammatory reactions and recruits other immune cells (Beghdadi et al, 2011; Dudeck et al, 2018). MCs have recently been shown to degranulate in response to a component of the fungal cell, β-glucan, with a unique response pattern with included release of histamine and β-hexosaminidase but not LTC4, IL-6, or CCL2 (Barbosa-Lorenzi et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…The remote effect of MC-derived TNF may be explained by its storage in the proteoglycan-backbone of the secretory granules. Importantly, we and others were able to visualize in vivo that the secretory granules are released by peripheral MCs in an intact and stable form [8,67,68]. Mediators such as histamine that are not highly charged rapidly diffuse from the proteoglycan matrix upon MC granule secretion to the extracellular fluid.…”
Section: Functions In Ln Conditioning and Hypertrophymentioning
confidence: 92%